1963
DOI: 10.1029/jz068i019p05421
|View full text |Cite
|
Sign up to set email alerts
|

Very-Low-frequency phase observations of solar flare ionization in the D region of the ionosphere

Abstract: Sudden phase anomalies produced by solar flares have been observed simultaneously on several long VLF propagation paths. The paths providing useful data are NBA (18 kc/s) Panama to Boulder, Colorado; to Maui, Hawaii; to Frankfort, Germany; and to College, Alaska; and GBR (16 kc/s) Rugby, England, to Boulder; and NPG (18.6 kc/s) Seattle to College, Alaska. The observations show that during a solar flare the magnitude of the mean change of reflection height Δh on each sunlit path can apparently be related to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

1964
1964
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…The duration of SPA event, i.e., the time from the beginning of the event to recovery normally varies from 30 minutes to 2-3 hours (Chilton et al, 1963). In the present investigation, though the duration varied from 16 minutes to 100 minutes, it is observed that over 65% of the SPAs lasted between half an hour to one hour as seen in Fig.…”
Section: Duration Of Spa Eventsmentioning
confidence: 40%
“…The duration of SPA event, i.e., the time from the beginning of the event to recovery normally varies from 30 minutes to 2-3 hours (Chilton et al, 1963). In the present investigation, though the duration varied from 16 minutes to 100 minutes, it is observed that over 65% of the SPAs lasted between half an hour to one hour as seen in Fig.…”
Section: Duration Of Spa Eventsmentioning
confidence: 40%
“…This results in a lowering of the reflection height of VLF signals and SPA's occur (CHILTON et al, 1963(CHILTON et al, , 1965. So, it becomes necessary to know phase changes during solar flares for the detection of SPA's.…”
Section: Measurements Of Sudden Phase Anomalies (Spa's)mentioning
confidence: 99%
“…The distribution of the duration of SPA events is already reported as from 30 minutes to 2 or 3 hours (CHILTON et al, 1963). Using the data of 682 SPA events observed on NWC-Toyokawa circuit from 1971 to 1974, a histogram of the duration of SPA events is obtained as shown in Fig.…”
Section: Duration Of Spa Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…These ionization enhancements are detected as abrupt phase variations of the VLF signals, the called sudden phase anomalies (SPAs). The size of the SPAs depends on the XͲray flare fluxes (Chilton et al, 1963;Crombie, 1965;Grubor et al, 2005;Kaufmann et al, 2002;McRae and Thomson, 2004). SPA studies have shown that the DͲregion conductivity and reference height present different characteristics as a function of the solar activity level.…”
Section: Introductionmentioning
confidence: 99%